PENDAPAT TOKOH NAHDLATUL ULAMA DAN MUHAMMADIYAH PROBOLINGGO TENTANG KUA SEBAGAI TEMPAT PERNIKAHAN SEMUA AGAMA - Nanang Suhartono; Ana Billah (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Marriage regulations in Indonesia are regulated in Marriage Law Number 1 of 1974. Article 2 states that "every marriage is recorded in accordance with applicable laws and regulations" meaning that every marriage must be recorded in accordance with applicable regulations. However, in practice, marriage registration at the KUA is only assigned to Muslims. Meanwhile, registration of non-Muslim marriages is not regulated in detail. So, the Minister of Religion has a discourse that KUA will be a wedding venue for all religions. From this description, this research focuses on the views or opinions of Nahdlatul Ulama and Muhammadiyah figures in Dringu District in responding to this discourse. The research method used in this research uses empirical research methods, namely a type of research that is oriented to an empirical field approach. This research uses a qualitative approach, namely collecting data to obtain new understanding from sources regarding the issues that occur. The location of this research was carried out in Dringu District, Probolinggo. The results obtained in this research were that NU figures thought that this discourse was a good breakthrough because it made it easier for non-Muslims to register their marriages. Meanwhile, Muhammadiyah figures are of the opinion that the discourse must be reviewed by considering problems that will arise such as technical and implementation readiness as well as non-Muslim experts for non-Muslim minority areas. Keywords: Opinion; Nahdlatul Ulama; Muhammadiyah; KUA; Marriage of All Religions